IMPLEMENTASI PRINSIP KERJA SAMA DALAM WACANA LISAN BAHASA MELAYU DIALEK KETAPANG - Wahyu Damayanti (tuahtalino, 2017)
The purpose of this study to obtain a description of the implementation of the principles of cooperation in the Malay dialect speech Ketapang detailed in the four issues of the implementation of (a) the maxim of quantity, (b) the maxim of quality, (c) the maxim of relevance, and (d) the maxim of ways. The study used a pragmatic approach as presented Grice, particularly in terms of the principles of cooperation with four kinds of maxims, namely (a) the maxim of quantity, (b) the maxim of quality, (c) the maxim of relevance, and (d) the maxim of ways. That is, the discussion focused on the realization of the four maxims in the utterances of Ketapang Malay dialect. The method used is descriptive qualitative method aided with a unified method pragmatic. The results of the study with the theories and methods are manifest in the utterances Ketapang Malay dialect which shows the implementation of the principle of cooperation. Utterances formed with the principles of cooperation shows certain characteristics.